2023
DOI: 10.3390/antiox12030630
|View full text |Cite
|
Sign up to set email alerts
|

The Chelating Ability of Plant Polyphenols Can Affect Iron Homeostasis and Gut Microbiota

Abstract: In the past decades, many studies have widely examined the effects of dietary polyphenols on human health. Polyphenols are well known for their antioxidant properties and for their chelating abilities, by which they can be potentially employed in cases of pathological conditions, such as iron overload. In this review, we have highlighted the chelating abilities of polyphenols, which are due to their structural specific sites, and the differences for each class of polyphenols. We have also explored how the diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 193 publications
2
18
0
Order By: Relevance
“…Plant polyphenols are known scavengers of free radicals due to their hydroxyl H‐atom transfer abilities to form stable phenoxy radicals (Chen et al ., 2020). Polyphenols also have iron chelating ability by binding to iron (Scarano et al ., 2023). Thus, it is plausible that the high polyphenol and flavonoid contents of the peel extract obtained at 78 °C influenced its higher radical scavenging (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plant polyphenols are known scavengers of free radicals due to their hydroxyl H‐atom transfer abilities to form stable phenoxy radicals (Chen et al ., 2020). Polyphenols also have iron chelating ability by binding to iron (Scarano et al ., 2023). Thus, it is plausible that the high polyphenol and flavonoid contents of the peel extract obtained at 78 °C influenced its higher radical scavenging (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The potential health benefits of polyphenols in general are classically attributed to their potential to prevent oxidative damage to cells and tissues. In fact, in vitro studies have demonstrated that many polyphenols are efficient “scavengers” of oxidative species (Scarano et al., 2023). They can also act as chelators of transition metal ions, thereby preventing the formation of initiating radicals catalyzed by iron and copper (Rice‐Evans et al., 1996).…”
Section: Health Benefits Of Wine Phenolic Compoundsmentioning
confidence: 99%
“…Excessive iron, reckoned as a risk factor for cancer, can induce ROS formation and lead to mutation and cellular damage. Consumption of red meat elevated the risk of some malignancies like esophageal cancer, colorectal cancer, etc., which may be associated with excessive heme-iron intake (Seiwert et al, 2020). That may be attributed to the Fenton reaction, ROS formation, and subsequent DNA damage, which are considered as potential induction agents of cancer.…”
Section: Polyphenols-induced Iron Starvation For Cancer Therapymentioning
confidence: 99%
“…After being taken into the digestive system, Fe 3+ will be reduced by duodenal cytochrome B (Dcytb) and then transported into duodenal enterocytes by divalent metal cation transporter 1 (DMT1), later stored as ferritin or exported to plasma via basolateral iron exporter: Fpn (Figure 1) (Vogt et al., 2021). Plenty of evidence has demonstrated that dietary polyphenols would interfere with intestinal nonheme iron absorption, including myricetin, quercetin, tannin, and their derivatives (Scarano et al., 2023). Vegetables and fruits which are rich in polyphenols like black beans, red grape, green tea, and grape seed extract, present remarkable inhibitory effects on iron availability (Pap et al., 2021).…”
Section: Iron Intake Absorption and Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation